Induction of Salinity Tolerance through Seed Priming with Chenopodium Salt Bladders in Rice (Oryza sativa L.) and Black gram (Vigna mungo L.) - R VINOTHINI; K RAJA (Seed Research, 2024)
Chenopodium is a halophytic plant has the ability to absorb salt from soil and deposits in aerial plant parts, more particularly in leaves. It helps the plant to survive in salinity affected soil conditions. The morpho-physiological characters of the plant act as protective mechanism against mechanical damages, pests, excessive light and drought. Also, salt bladders have macro and micro nutrients. Therefore, experiments were conducted to induce salt tolerance in rice and black gram through seed priming treatment with the salt glands of Chenopodium. The results showed that the seed quality parameters such as germination, speed of germination, seedling vigour etc. were reduced with the increase in the salinity concentrations irrespective of the treatments. In addition, both the seeds tolerated the salinity level upto 75 mM NaCl with good seed quality attributes. The rice seeds treated with Chenopodium salt bladder @ 0.6 per cent have recorded higher germination (72 %) than the control (36 %) under 100 mM salinity condition. Seedling survival was also higher (67 %) in this saline condition due to Chenopodium treatment. Similarly, the black gram seeds primed with Chenopodium salt bladder @ 0.2 per cent have recorded higher germination (71 %) at 75 mM NaCl concentration than the control (65 %) and the rate of survival is also better in case of Chenopodium salt bladder (52 %) than the control (48 %). Consequently, it is concluded that the Chenopodium salt bladder can be used to treat the rice and black gram seeds for the induction of salt tolerance of upto 75 mM saline level.